THE ROLE OF FACILITIES IN THE CONTINUITY OF FISH LANDING ACTIVITY AT THE KUALA TUNGKAL BEACH FISHERIES PORT, WEST TANJUNG JABUNG, JAMBI PROVINCE - Riah Ukur Tumangger; Alit Hindri Yani; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted on July 6, 2018 at Kuala Tungkal Beach Fisheries Port (PPP), West Tanjung Jabung, Jambi Province. The purpose of this study was to determine the role of facilities that support the continuity of fish landing activity at the Kuala Tungkal Beach Fisheries Port (PPP). The data was gathered through direct observation, questionnaires and interviews with respondents. Facilities play a role in supporting the continuity of fishing port’s operation. Insufficiency or unavailability from one of the necessary facilities would inhibit the continuity of the port’s operation. This problem is often found in many fishing ports. Kuala Tungkal Beach Fisheries Port is one of the only type C fishing ports in Jambi Province which opens opportunities for investors both from within and outside the country. The analysis was done descriptively after identification of existing facilities and activities and recalculation of the capacity place for fish auction, dock and port pool. One of the facilities of fish landing activity in Kuala Tungkal Beach Fisheries Port (PPP), such as the fish auction place (TPI), is not used by fishermen so the utilization rate cannot be calculated. For dock facilities it has 80 m length and 2 m depth. Based on the calculation results showed that the required loading length is 27.14 m and the utilization rate is 6.88% and for port pool facilities it has 600 m2 area and 2 m depth. Based on the calculation of the required port pool area is 8.029.236 m2 with the utilization rate is 3.44%.Keywords: port facilities, fishing port, PPP Kuala Tungkal